Exclusive Breastfeeding for Six Months: the WHO Six Months Recommendation in the Asia Pacific Region - Binns, Colin; Lee, M. (HEC Press, 2014)
In 2001 the World Health Assembly adopted the infant feeding strategy which included the recommendation for exclusive breastfeeding until 6 months of age with continued breastfeeding while complementary foods are introduced. This recommendation has been endorsed by many national authorities, professional organisations and most countries in the Asia Pacific Region. Reviews by WHO, the US Surgeon General, Agency for Healthcare Research and Quality, US Department of Health and Human Services and others have documented the many benefits of breastfeeding. The introduction of solid foods before six months of age is associated with increased rates of infection, reduced breastmilk production, disruption to the microbiome and possibly obesity. If solids are introduced at around six months (by 26 weeks) there is no evidence of increases in allergic diseases.